THE INFLUENCE OF LEADERSHIP, COMPETENCY, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE IN THE BATANG SERANG DISTRICT DISTRICT OFFICE - David Harefa; Hendra Nazmi; Julfita Br sukatendel; Fourti dayanti zai; Sri Puspa Dewi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Employee performance is the main thing that must be considered in work activities. This research aims to determine the influence of leadership, competency and organizational culture on the performance of employees at the Batang Panggang District Subdistrict Office. The population in this study were all 32 employees of the Batang Panggang Subdistrict District Head Office. This type of research uses a quantitative approach and technical data analysis uses multiple linear regression analysis. This type of research concludes that leadership has an influence on employee performance, competence has no influence on employee performance, and organizational culture has no influence on employee performance.